2020
DOI: 10.1002/lary.29275
|View full text |Cite
|
Sign up to set email alerts
|

Crumley's Classification of Laryngeal Synkinesis: A Comparison of Laryngoscopy and Electromyography

Abstract: Objectives/Hypothesis Applying the principles of misdirected nerve regeneration to the larynx, Roger Crumley in 1989 coined the term laryngeal synkinesis (LS) which he later (2000) classified into 4 types (type I – good voice, type II – involuntary twitches and poor voice, type III – adduction during inspiration, type IV – abduction during phonation). Neurophysiological data were not available for all LS patients at that time. The current study was undertaken to utilize and test the Crumley classification for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Conversely, regenerative potential was more commonly observed in patients with a disease duration exceeding 3 months. 18 That is also the reason why The involvement of SLN and CM in IVCP is a topic of interest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, regenerative potential was more commonly observed in patients with a disease duration exceeding 3 months. 18 That is also the reason why The involvement of SLN and CM in IVCP is a topic of interest.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that denervated potential was frequently observed in the PCM and TM of patients with unilateral vocal cord paralysis who had a disease duration of 1–3 months, and our findings indicate that the average disease duration of IVCP patients with paralysis on the left or right side was similar (nearly 45 days), and both of them were less than 3 months. Conversely, regenerative potential was more commonly observed in patients with a disease duration exceeding 3 months 18 . That is also the reason why we chose 3 months as a differentiation point for disease course to analyze the differences of voice indicators and LEMG results in IVCP patients with left or right vocal fold paralysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important, since the patterns of synkinetic reinnervation in the larynx seem to be etiology-dependent. The rates of synkinetic activity in the posterior cricoarytenoid (PCA) muscle in comparison to the thyroarytenoid (TA) muscle are different dependent on the etiology ( 31 ), and the laryngoscopic classification might be different from the EMG classification ( 32 ). As it is the case for facial nerve injuries, not much is known about the time course of the laryngeal muscle atrophy.…”
Section: Facial or Recurrent Laryngeal Nerve Lesion And Time Course O...mentioning
confidence: 99%